Behavioral biomarkers for calf health - Ruiz, Luke A. (Kansas State University, 2019)
Applied ethology is a diverse scientific field studying animals in confinement under human management. Data collection techniques including automated measures (e.g. activity monitors and environmental enrichment devices) and video recording systems aid in collecting animal behavior data while reducing more invasive collection measures. Understanding early life behavior’s in both dairy and beef calves is important for the health, performance, and welfare of these animals. Oral behaviors early in life can affect a calf’s performance and health through adulthood. Applied ethologist utilize automated technologies to better quantify the behaviors of dairy and beef calves early in life which could result in changes in management of calves. In the first study, the objectives were to validate an environmental enrichment device for individually housed Holstein dairy calves and describe methods for behavioral data collection. Holstein bull calves were fitted with 3-axis accelerometers (activity monitor) and provided an environmental enrichment device. A total of 59 h of video footage was analyzed for calf behaviors. Observed EED use was shown to be highly correlated with automated EED. Observed standing and lying durations were correlated with automated standing and lying durations. Use of environmental enrichment can aid in collection of data and allow animals to express natural behaviors such as suckling. Furthermore, data collected through automated techniques can give valuable knowledge without increasing distress to animals and providing more time efficient methods of data collection. In the second study, the objective was to determine if calf behavior data collection techniques (both direct observation and automated) would correlate with measures of passive transfer of immunity (hematocrit; total plasma protein; Immunoglobulins, IgG1 and IgM). Variables collected included: each calf’s first-meal suckling behaviors; automated activity behaviors, and measures of passive transfer of maternal antibodies (IgG1, Igm, hematocrit, and total plasma protein). There was a tendency for IgG1 concentrations to have an inverse relationship with calf body weight. Total plasma protein was correlated with IgG1 and IgM. Likewise, hematocrit was correlated with IgG1 and IgM. Total Plasma Protein had an inverse relationship with birth-to-stand intervals. In addition, total plasma protein tended to decrease as the birth-to-suck interval increased. Total plasma protein increased with the number of lying-bouts per day for the first week of life. Furthermore, there was a tendency for the birth-to-last teat suckled to decrease as the temperature on the day of birth increased. Calf lying duration during the first week of life increased as the temperature on the day of birth increased. These data demonstrate calf behaviors early in life are associated with measures of passive transfer of immunity. Overall, these data support the use of applied ethology techniques including live/video observation and automated data collection to help address early life behaviors in both dairy and beef cattle. Automated technologies such as an environmental enrichment device could help collect important sucking behavior data while providing dairy calves an avenue to satiate their motivation to suck. Furthermore, observed behavioral measures such as the birth-to-stand measure in beef calves, can give an indication to their passive transfer of immunity status. Future research in regards to animal behavior could benefit from the use of video recording systems and automated technologies resulting in better management of animals under human care.
Keywords: Bovine calves; Applied ethology; Behavior; Immunity